Kinetic Properties of Polyphenol Oxidase Obtained from Various Olives (Olea europa L.) - Gencer, Nahit; Sinan, Selma; Arslan, Oktay (Asian Journal of Chemistry, 2012)
In this study, the biochemical properties of olive polyphenol oxidase (PPO) which are known to be the primary reason for enzymatic browning, have been investigated. The polyphenol oxidase of Olea europaea L. cultivars (Domat, Kiraz, Uslu, Gemlik and Ayvalik) was used for enzyme source. It was found that the optimum pH values were 6.5 with four cultivars except DPPO for catechol as substrate. Optimum pH value was 7.0 for DPPO enzyme. UPPO has the most activity toward catechol, due to the lowest KM (5.74 mM) and the biggest Vmax/KM (1249.93) values. The enzyme had a temperature optimum at 40 ºC and was relatively stable at 50 ºC, with 55 % loss of activity approximately. APPO and KPPO activity lasted until 1 h at 60 ºC. At 60 ºC, heat denaturation of the DPPO, UPPO and GPPO enzymes occurred.